Determinants Of Bos Fund Management On The Productivity Of Smk Performance With Financial Management Effectiveness As A Mediation Variable - Meidytha Puti Sabrina; Dewi Sartika (CV. Doki Course and Training, 2026)
This study aims to analyze the influence of planning the use of School Operational Assistance (BOS) funds, implementation and distribution of BOS funds, and managerial competence on the productivity of Vocational High School (SMK) performance in Palembang City with the effectiveness of financial management as a mediating variable. This study uses a quantitative approach with a survey method on 20 public and private vocational high schools in Palembang City with a total of 100 respondents consisting of principals, school treasurers, school committees, and teachers directly involved in BOS fund management, with a saturated sampling technique. Data were collected through a questionnaire using a Likert scale and analyzed using the Partial Least Square–Structural Equation Modeling (PLS-SEM) method. The results of the study indicate that planning the use of BOS funds, implementation and distribution of BOS funds, and managerial competence have a positive and significant effect on the effectiveness of financial management, and the effectiveness of financial management also has a positive and significant effect on the productivity of SMK performance. In addition, the effectiveness of financial management is proven to be able to mediate the influence of planning the use of BOS funds, implementation and distribution of BOS funds, as well as managerial competence on the productivity of SMK performance, so that increasing the productivity of SMK performance can be achieved through planned, targeted management of BOS funds, and supported by strong managerial competence.